Getting the numbers right - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
Hohenheim, 1996: Strengthening biometry and statistics in agricultural research. CTA, 1997. 173 pp. ISBN 92 9081 1676 CTA number 850. 20 credit points